A Review on Hydrogen Supplementation in Compression Ignition Engines (International Journal of Current Engineering and Technology, 2015)
This paper highlights the Hydrogen utilization in internal combustion engines and mainly focuses on compression ignition engines. This hydrogen utilization is either pure or as supplemented. Further, the paper tries to synchronize the past experience of the researchers to very recent efforts of the experts of this area. Mainly the paper also discusses the various undesirable phenomena and its effects on engine performance and emission variations and their remedies with reference to hydrogen introduction and induction in compression ignition engines. Also presents the importance of direct and indirect injection with reference to application of alternative fuels. The study is divided to include, theoretical and experimental investigations on hydrogen supplementation. Theoretical studies included the modeling and simulation, artificial neural network modeling and genetic algorithm optimization while the experimental investigations included the hydrogen direct injection technique, hydrogen indirect injection / induction technique, exhaust gas recirculation (EGR) with hydrogen-diesel, diluents with hydrogen-Diesel, biodiesel with hydrogen-diesel or with diesel alone and additives with hydrogen-diesel or with diesel alone
Keywords: Hydrogen; supplemented fuel; Internal Combustion engine; compression ignition engine